(untitled) (Eurasian Research Bulletin, 2023)
Our article discusses the problem of designing the communication space of students and future teachers as a means of improving pedagogical communication. The authors show approaches; You will get acquainted with the semantic accents to understand the communicative abilities and the conditions of their appearance